Biological control of potato common scab by Bacillus amyloliquefaciens Ba01 - Lin, Chih (PLoS One, 2018)
Potato common scab, which is caused by soil-borne Streptomyces species, is a severe plant disease that results in a significant reduction in the economic value of potatoes worldwide. Due to the lack of efficacious pesticides, crop rotations, and resistant potato cultivars against the disease, we investigated whether biological control can serve as an alternative approach. In this study, multiple Bacillus species were isolated from healthy potato tubers, and Bacillus amyloliquefaciens Ba01 was chosen for further analyses based on its potency against the potato common scab pathogen Streptomyces scabies. Ba01 inhibited the growth and sporulation of S. scabies and secreted secondary metabolites such as surfactin, iturin A, and fengycin with potential activity against S. scabies as determined by imaging mass spectrometry. In pot assays, the disease severity of potato common scab decreased from 55.6 ± 11.1% (inoculated with S. scabies only) to 4.2 ± 1.4% (inoculated with S. scabies and Ba01). In the field trial, the disease severity of potato common scab was reduced from 14.4 ± 2.9% (naturally occurring) to 5.6 ± 1.1% after Ba01 treatment, representing evidence that Bacillus species control potato common scab in nature.